Racism and judicial corruption in the US (2016)
Is racial hate reflected in the degree of judicial corruption? Using US state-level data, we find racial hate to be a positive and statistically powerful predictor of judicial corruption. This relationship prevails after the inclusion of the conventional control variables and regional fixed effects. In terms of magnitude, one standard deviation increase of racial hate relates to an increase of 70 percent of one standard deviation in corruption. Interestingly, no such relationship can be found for corruption in the executive or legislative branch.